Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1134/s1560354707030021
|View full text |Cite
|
Sign up to set email alerts
|

Separation of variables in the generalized 4th Appelrot class

Abstract: We consider the analogue of the 4th Appelrot class of motions of the Kowalevski top for the case of two constant force fields. The trajectories of this family fill the four-dimensional surface O in the six-dimensional phase space. The constants of three first integrals in involution restricted to this surface fill one of the sheets of the bifurcation diagram in R 3 . We point out the pair of partial integrals to obtain the explicit parametric equations of this sheet. The induced system on O is shown to be Hami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
0
11
0
8
Order By: Relevance
“…The sets M 1 and M 2 are smooth four-dimensional manifolds, though M 2 is non-orientable (see [27,33]). Using the explicit parametric equations of the set M 3 obtained in [34] (see also [30]) it can be shown that M 3 is a smooth four-dimensional manifold everywhere except for the points common with M 4 . At these points M 3 has a transversal self-intersection which is the two-dimensional manifold M 3 ∩ M 4 with boundary.…”
Section: Description Of Critical Subsystems and Classes Of Singularitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sets M 1 and M 2 are smooth four-dimensional manifolds, though M 2 is non-orientable (see [27,33]). Using the explicit parametric equations of the set M 3 obtained in [34] (see also [30]) it can be shown that M 3 is a smooth four-dimensional manifold everywhere except for the points common with M 4 . At these points M 3 has a transversal self-intersection which is the two-dimensional manifold M 3 ∩ M 4 with boundary.…”
Section: Description Of Critical Subsystems and Classes Of Singularitiesmentioning
confidence: 99%
“…[35]) that on a manifold defined as a common level of two independent functions such degeneration takes place on a subset of zeros of the Poisson bracket of these functions. At the points of the subsystems M i the following identities hold [27,28,34]…”
Section: Description Of Critical Subsystems and Classes Of Singularitiesmentioning
confidence: 99%
“…§ 3. Критические подсистемы и бифуркационные диаграммы В этом разделе излагается сводка результатов [12,13,23,24], относящихся к нахождению критического множества отображения момента (1.5) и бифуркационных диаграмм. Приво-дится система единых обозначений, необходимая для трехмерной классификации.…”
Section: § 1 введениеunclassified
“…Эти множества обладают еще одним важным свойством, которое оказывается связанным с вырожденностью критических точек в P 6 , а именно, как показано в работах [14], [15], [28], на множествах M i ∩ F −1 (∆ i ) (i = 1, 2, 3) вырождается 2-форма, индуцированная на M i сим-плектической структурой многообразия P 6 . Заметим, что внутри M 1 соответствующие точки регулярны, внутри M 2 , M 3 регулярны почти все из них (за исключением точек пересечения с C 1 ).…”
Section: она приводит интегралы к видуunclassified
See 1 more Smart Citation